2015
DOI: 10.1007/s00038-015-0658-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trends in good self-rated health: effects of age and birth cohort in a 25-year follow-up study in Sweden

Abstract: Longitudinal trends in good self-rated health: effects of age and birth cohort in a 25-year follow-up study in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
9
30
0
5
Order By: Relevance
“…Increased availability of psychosocial interventions in health care centers, such as psychologists, could also be valuable. Our recently published study of the same study population showed a trend of deteriorating self-rated health in young adults, between 1980 and 2005, which further points out the vulnerability of this young age group [24]. …”
Section: Discussionmentioning
confidence: 90%
“…Increased availability of psychosocial interventions in health care centers, such as psychologists, could also be valuable. Our recently published study of the same study population showed a trend of deteriorating self-rated health in young adults, between 1980 and 2005, which further points out the vulnerability of this young age group [24]. …”
Section: Discussionmentioning
confidence: 90%
“…Previous studies suggested that the temporal developments of SRH differ across ages [9,13,27], thus calling for an age-specific approach in analyzing health trends. Within the context of an ageing population, the German government decided to rise the statutory retirement age gradually up to the age of 67 in order to keep the pension system financially sustainable [28].…”
Section: Introductionmentioning
confidence: 99%
“…Ikäihmisten koettu terveys on aikaisempien tutkimusten perusteella kohentunut vuosien saatossa (Leinonen, Suominen, Sakari-Rantala, Laukkanen & Heikkinen 2006;Leskinen ym. 2010;Galenkamp, Braam, Huisman & Deeg 2012;Helldán & Helakorpi 2014;Johansson, Midlöv & Sundquist 2015;Giron 2016). On havaittu, että suomalaisten ikäihmisten koettu terveys on parantunut tasaisesti 1990-luvun alusta alkaen (Helldán & Helakorpi 2014).…”
Section: Johdantounclassified
“…2006;Galenkamp ym. 2012;Helldán & Helakorpi 2014;Johansson, Midlöv & Sundquist 2015). Tämän tutkimuksen tulokset tukevat aikaisempien tutkimusten havaintoja.…”
Section: Pohdintaunclassified